Temporal dynamics of drinking water sodium levels in coastal areas, Cyprus 2009-2020 - Xeni, Christina; Gribble, Matthew O.; Oude Essink, Gualbert H P; Fleming, Lora E; Makris, Konstantinos C. (My University, 2024)
Around the world, groundwater salinity levels are increasing in coastal areas, as a result of its systematic overexploitation for domestic, agricultural and industrial demand and potentially due to climate change manifestations (such as, sea level rise). We hypothesized that the groundwater quality of many Mediterranean coastal areas is already being perturbed, especially for water salinity, depending on the groundwater distance from the seafront. The objectives of this study were: i) to evaluate the magnitude and temporal variance of drinking water sodium (Na) as a metric of salt intake used for public health purposes using drinking water data in Cyprus; and ii) to examine the degree of Na enrichment in drinking water as defined by the seawater coastline distance of each sampling point. Open access governmental data of drinking water Na (n = 3304), daily max ambient air temperature and total rainfall were obtained for the period of 2009-2020 from governmental repositories. Linear mixed-effect regression models of drinking water Na with unsupervised covariance matrix were used. After adjusting for temperature and rainfall data, there was a significant annual increase in drinking water Na levels over time (beta = 0.01; 95 % CI: 0.00, 0.02; p = 0.02) for the coastal areas (<10 km from coastline, cutoff used by the EU Environment Agency), but this was not the case for non-coastal areas (>10 km distance from coastline). The distance of each sampling point from the coastline in Cyprus was negatively associated with drinking water Na in coastal areas (beta = -0.04, 95%CI: -0.06, -0.01; p = 0.002); this was not the case for non-coastal areas. More research is warranted to better understand the impacts of global environmental change on water quality in association with the burden of disease in coastal areas.
Keywords: Blood pressure; Coastal; Drinking water; Groundwater; Public health; Salinization; Salt; Sodium